Dictators and their secret police coercive institutions and state violence - Greitens, Sheena Chestnut (Studies of the Weatherhead East Asian Institute, Columbia University., 2016)
"How do dictators stay in power? When, and how, do they use repression to do so? Dictators and their Secret Police explores the role of the coercive apparatus under authoritarian rule in Asia - how these secret organizations originated, how they operated, and how their violence affected ordinary citizens. Greitens argues that autocrats face a coercive dilemma: whether to create internal security forces designed to manage popular mobilization, or defend against potential coup. Violence against civilians, she suggests, is a byproduct of their attempt to resolve this dilemma. Drawing on a wealth of new historical evidence, this book challenges conventional wisdom on dictatorship: what autocrats are threatened by, how they respond, and how this affects the lives and security of the millions under their rule. It offers an unprecedented view into the use of surveillance, coercion, and violence, and sheds new light on the institutional and social foundations of authoritarian power" -- Provided by publisher.